The effect of freeze–thaw and storage on African swine fever virus detection in environmental samples - Kwon, Taeyong; Gebhardt, Jordan T.; Lyoo, Eu Lim; Gaudreault, Natasha N.; Trujillo, Jessie D.; Richt, Juergen A. (Frontiers in Veterinary Science, 2025)
African swine fever is a devastating viral disease of swine causing up to 100% mortality and significant impacts to the swine industry. The causative agent, African swine fever virus (ASFV), is a large, enveloped virus containing a linear, double-stranded DNA genome with 170–190 kb in length. Since its introduction into the Caucasus region in 2007, the genotype II ASFV has continued to spread to Europe, Asia, and Caribbean countries. Early detection is crucial to prevent and control ASF outbreaks for biosecurity purposes, and environmental samples can be used to evaluate the level of biosecurity. Therefore, we evaluated the effect of freeze–thaw cycles and storage at 4°C and room temperature (RT) on ASFV DNA detection in environmental samples. ASFV DNA was stable in environmental samples with no organic contaminants after freeze–thaw and incubation at 4°C and RT. However, incubation at RT negatively affects ASFV detection in swine feces and feed dust samples that were collected using premoistened gauze. There were significant reductions in ASFV detection in environmental samples in the presence of soil and organic mixture after freeze–thaw and incubation at 4°C and RT. These results provide novel insights on the appropriate storage of environmental samples for ASFV detection and contribute to the control and prevention of ASF outbreaks and new introductions.